Cold Therapy pada Luka Operasi Ortopedi - Nugraheni, Auliya Tunnisaa; Masfuri, Masfuri (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of the cooling method on overcoming acute responses such as pain after surgery. It has three main effects: reducing pain (analgesia), anti-inflammatory effects, and edema/swelling. The method used was a systematic search for articles with a randomized controlled trial (RCT) research design through the PubMed, ProQuest, ScienceDirect, and ClinicalKey databases from October 2013 to October 2023 using the keywords "post-surgical" OR "after surgery" OR "post-operative" AND "iced pack" OR "cold packs" AND "acute pain" OR "pain management" OR "therapy." The search results revealed that six articles were obtained from 696 articles through screening based on inclusion and exclusion criteria. Research shows that the cooling method can be applied to orthopedic patients and positively impacts the acute response after surgery. Conclusions show that this method can significantly reduce the effects of acute inflammation after surgery and restore optimal function with the standard protocols related to this method.This study aims to determine the effect of the cooling method on overcoming acute responses such as pain after surgery. It has three main effects: reducing pain (analgesia), anti-inflammatory effects, and edema/swelling. The method used was a systematic search for articles with a randomized controlled trial (RCT) research design through the PubMed, ProQuest, ScienceDirect, and ClinicalKey databases from October 2013 to October 2023 using the keywords "post-surgical" OR "after surgery" OR "post-operative" AND "iced pack" OR "cold packs" AND "acute pain" OR "pain management" OR "therapy." The search results revealed that six articles were obtained from 696 articles through screening based on inclusion and exclusion criteria. Research shows that the cooling method can be applied to orthopedic patients and positively impacts the acute response after surgery. Conclusions show that this method can significantly reduce the effects of acute inflammation after surgery and restore optimal function with the standard protocols related to this method. Keywords: Cryotherapy, Cold Compress, Orthopedics, Post-Operation